Genetic Diversity and Genotype Distribution of Erwinia amylovora in Korea - Hyeonheui Ham; Se-Weon Lee; Yong Hwan Lee (The Plant Pathology Journal)
Erwinia amylovora, first identified in 1793 in Hudson Valley (New York, USA), has a genome size of 3.7–4.0 Mb. E. amylovora bacterial strains are classified based on the infecting hosts: the Amygdaloideae-infecting (AI) group, targeting apple and pear trees, and the Rubus-infecting group, affecting berry trees. Since the AI-group strains display high genetic similarity (>99.7%), it is challenging to characterize their genotypes. This study investigated the genetic diversity of E. amylovora isolates in Korea and the regional distribution patterns of genotypes using a multilocus variable number of tandem repeat analysis (MLVA). Four specific primers were used to amplify and sequence tandem repeats in the E. amylovora genome, and a distribution map of E. amylovora was created using MLVA genotypes. Thirty-two types of MLVA patterns were identified in Korean strains, and RV19 was the dominant type identified in all South Korean regions. According to the minimal spanning tree, genotypes were differentiated into RV7, RV14, RV20, RV22, and RV27 types, originating from the RV19 type. This finding suggests that the RV19 type, introduced to Korea for the first time, spread to other regions from Anseong-si, Cheonan-si, Chungju-si, and Jecheon-si, depending on the type. We determined the MLVA genotypes of E. amylovora isolates and distribution patterns by region from 2019 to 2023. The distribution of these genotypes by year and region provides basic information for the genetic diversity and spread of E. amylovora in Korea.